Bacopa monniera recombinant mevalonate diphosphate decarboxylase: biochemical characterization - Shakeel Abbassi; Vishwakarma, Rishi K.; Patel, Parth; Kumari, Uma; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2015)
Mevalonate diphosphate decarboxylase (MDD; EC 4.1.1.33) is an important enzyme in the mevalonic acid pathway catalyzing the Mg2+-ATP dependant decarboxylation of mevalonate 5-diphosphate (MVAPP) to isopentenyl diphosphate (IPP). Bacopa monniera recombinant MDD (BmMDD) protein was overexpressed in Escherichia coli BL21 (DE3) strain and purified to apparent homogeneity. K-m and V-max for MVAPP were 144 mu M and 52 U mg(-1) respectively. The values of turnover (k(cat)) and k(cat)/K-m, for mevalonate 5-diphosphate were determined to be 40 s(-1) and 2.77 x 10(5) M-1 s(-1) and k(cat) and k(cat)/K-m values for ATP were found to be 30 s(-1) and 2.20 x 10(4) M-1 s(-1), respectively. pH activity profile indicated the involvement of carboxylate ion, lysine and arginine for the activity of enzyme. The apparent activation energy for the BmMDD catalyzed reaction was 12.7 kJ mol(-1). Optimum pH and temperature for the forward reaction was found to be 8.0 and 45 degrees C. The enzyme was most stable at pH 7 at 20 degrees C with the deactivation rate constant (K-d(*)) of 1.69 x 10(-4) and half life (t(1/2)) of 68 h. The cation studies suggested that BmMDD is a cation dependant enzyme and optimum activity was achieved in the presence of Mg2+. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Mevalonate diphosphate decarboxylase; pH activity profile; Phylogenetic analysis; stability